STRATEGY FOR INCREASING THE LEARNING QUR'AN HADITS QUALITY FOR THE STUDENTS’ RELIGIOUS CHARACTER - Kurniawan, Didik; Jaenullah, Jaenullah; Jannah, Siti Roudhotul; Setiawan, Dedi; Mispani, Mispani (Jurnal As-Salam, 2023)
This study aims to analyze the implementation of quality improvement strategies and the formation of students' religious character through learning Al-Qur’an Hadits. This study uses a descriptive qualitative method that explores the quality of learning the Al-Qur’an Hadits and implementing religious character at Madrasah Aliyah Negeri (MAN) 1 East Lampung: data collection techniques using interviews, observation, and documentation. The data obtained were analyzed using the inductive method according to Miles & Huberman, namely by data reduction, data presentation, and conclusion/verification. The data analysis results show that the quality improvement strategy in learning Al-Qur’an Hadits at MAN 1 East Lampung consists of a planning process with work meetings determining the curriculum while making RPP and syllabus. The organizing process is described by dividing teaching tasks, compiling learning schedules, and carrying out coordination. The learning process applies a learning system with an introductory session and implementation of core learning. In comparison, the evaluation process is divided into a written assessment using numbers and included in the school report card, as well as an oral assessment carried out accidentally by the policies of each teacher. Forming the students’ religious character through learning the Al-Qur’an Hadits becomes a quality standard that refers to the goals of national education in general, namely to create a capable and noble generation.